LncRNA UCA1 Promotes the Progression of AML by Upregulating the Expression of CXCR4 and CYP1B1 by Affecting the Stability of METTL14. (8th February 2022) - Li, Jiajia; Li, Zhongyu; Bai, Xue; Chen, Xiaofeng; Wang, Meng; Wu, Yanping; Wu, Haotian
Abstract : Objective . Increasing numbers of studies have proved that m6A methylation plays crucial roles in different cancers. However, how lncRNA regulates m6A methylation and participates in acute myeloid leukemia (AML) remains unclear. Therefore, this study aims to explore the function and mechanism of UCA1 in AML by regulating m6A methylation. Methods . qRT-PCR, western blot, and immunohistochemical staining were used to detect the expression of METTL14, CXCR4, and CYP1B1. qRT-PCR was used to detect the expression of UCA1. CCK8, flow cytometry, and transwell assays were used to detect the proliferation, apoptosis, migration, and invasion of HL60 and U937 cells, respectively. m6A methylation was detected by dot blot analysis. Tumor-bearing mice were established, and tumor weight and volume were analyzed. Immunofluorescence staining, co-localization, and RNA pull-down were used to confirm the reaction between UCA1 and METTL14. Results . Overexpression of UCA1 promotes AML development in vitro . Furthermore, we found that METTL14-influenced m6A methylation could be affected by UCA1. UCA1 promoted AML development by regulating m6A methylation. Moreover, the expression of CYP1B1 and CXCR4 was affected by METTL14. In addition, UCA1 promoted AML development by affecting m6A methylation in vivo . Conclusion . In the present study, we demonstrated that lncRNAUCA1 promotes the progression of AML by upregulating the expression of CXCR4 and CYP1B1 by affecting the stability of METTL14.